Conceptual Analysis Of Financial Behavior Model Through Systematic Literature Review - Miftakul Huda; Rengga Madya; Arie Gunawan; Budi Purnomo; Imas Purnamasari (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This study aims to determine the development and novelty of the financial behavior models most commonly used by researchers to predict financial actions. Methodology/approach – The research was conducted using a Systematic Literature Review approach by selecting articles from the Google Scholar index without limiting the year of publication so that all articles with financial behavior studies could appear. The reports were collected using publish or perish and then analyzed bibliometrically using VOS Viewer before being explored by abstraction and content. The flow of data selection in the study was carried out using the Prism method for 981 documents. Findings – The research results show that the study of financial behavior began in 1966 and continues to offer an increasing research trend. Models for describing the phenomenon of financial behavior continue to emerge, and one is mutually reinforcing with another. The models often discussed are the psychological model, the socialization model, the economic model, and the REMM model. Novelty/value – From the models discussed, a model has yet to be found to explain precisely the phenomenon of financial behavior in individual humans. These models are only alternatives, and it does not mean that one model can represent the complexity of human behavior toward finance; what is essential is the extent to which the model is consistent with the observed human behavior.